iTRAQ-Based Comparative Proteomic Analysis Reveals Molecular Mechanisms Underlying Wing Dimorphism of the Pea Aphid, Acyrthosiphon pisum - Song, Limei; Gao, Yuhao; Li, Jindong; Ban, Liping (Frontiers in Physiology, 2018)
Wing dimorphism is a widespread phenomenon in insects, with an associated trade-off between flight ability and fecundity. However, the mechanism at the molecular level of phenotypic plasticity is not entirely understood. In this study, we focused on the differential proteomics profiles between alate and apterous morphs of pea aphid, Acyrthosiphon pisum, using isobaric tags for relative and absolute quantitation (iTRAQ). A total of 5560 proteins were identified and 5528 proteins were quantified in the three biological replicates, of which 846 were differentially expressed between alate and apterous morphs. A bioinformatics analysis of differentially expressed proteins (DEPs) was performed based on gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). KEGG enrichment analysis showed that DEPs mainly participated in energy metabolism, amino acids biosynthesis and metabolism and signal sensing and transduction. To verify the proteomics data, the transcriptional expression of 29 candidate DEPs from iTRAQ were analyzed by quantitative real-time PCR (qRT-PCR), showing that 26 genes were consistent with those at proteomic levels. In addition, differentially expressed in several proteins that were linked to odorant-binding and chemosensory reception in alate morphs were detected. Quantitative real-time PCR revealed the tissue- and morph-biased expression profiles. The comparative proteomic analysis between alate and apterous morphs of pea aphid will help to facilitate our understanding of wing development and dimorphism in aphids at molecular levels.